REPRODUCTION PERFORMANCE OF WILD BROODSTOCK CORAL TROUT (Plectropomus leopardus) - Retno Andamari; Ketut Suwirya (Indonesian Fisheries Research Journal, 2010)
Coral trout is an important export commodity in many countries in southeast Asia. In Indonesia, the export of grouper currently relies on capture fisheries. To ensure sustainability of the wild catch as well as to develope mariculture, we need to better understand the performance of wild broodstock.